A Systematic Literature Review of Six Sigma Approach in Manufacturing and Services Industries in Indonesia - Maryani, Edna; Tampubolon, Salmon; Jaqin, Choesnul (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
The present work is a review of literature, to identify the improvements acquired from the application of the Six Sigma methodology in manufacturing and services industries in Indonesia. This systematic review intends to identify how manufacturing research is contributing to the development of the Industry in Indonesia agenda and for a broader understanding about the links between the manufacturing and services sectors. This systematic review intends to identify by mapping and summarizing existing research efforts, identifying research agendas, as well as gaps and opportunities for research development. The papers were selected base on relevant articles to the topic of work, and the bibliographic databases used for the research were the Google Scholar, ScienceDirect, ResearchGate, etc. The study counted on 50 articles to better exemplify these points, being 36 focused on the manufacturing sector and 14 on the services sector. In both sectors the variability of the process, improving process quality, productivity, efficiency, the service provided, increasing customer satisfaction, reducing costs, timeliness. It has been found that Six Sigma is a versatile tool that can be adapted and applied in any segment, allowing potential opportunities for new research and applications. Basic tools for brainstorming such as Pareto analysis and cause-effect analysis are definitely used in both industries: manufacturing and service.